Effects of pink guava (Psidium guajava) puree supplementation on antioxidant enzyme activities and organ functions of spontaneous hypertensive rat - Norazmir Md Nor; Ayub Mohd Yatim (Universiti Kebangsaan Malaysia, 2011)
This study was aimed to determine the effects of pink guava (Psidium guajava) puree supplementation on enzyme activities, kidney and liver function tests of Spontaneous Hypertensive Rats (SHR). Twenty-four male SHR were divided into four groups (control, CG (distilled water); low dosage group, LDG (0.5 g/kg body weight); medium dosage group, MDG (1.0 g/kg body weight); high dosage group, HDG (2.0g/kg body weight)). The rats were given pink guava puree via force-feeding and fed rat pellets ad libitum for 28 days in individual cages at 25±2°C. At the end of experiment, the rats were fast overnight (12 to14 h) and euthanized under an anesthetic condition with ether, and blood was collected from the portal vein or posterior vena cava. The specific activities of glutathione peroxidase (GPx) was significantly higher in LDG (2332.5±81.8 U/L), MDG (2424.8±97.1 U/L) and HDG (2594.6±82.8 U/L) respectively, as compared to CG (2171.8±65.9 U/L). Significant differences were also seen in glutathione reductase (GR) activities among all treated groups (LDG (132.5±11.8 U/L), MDG (141.5±16.4 U/L), HDG (148.8±13.2 U/L) compared to CG (126.1±14.2 U/L)). Liver function tests for total antioxidant status (TAS), alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH) and γ-glutamyl transpeptidase (GGT) showed significant differences in the treated group compared to control group. In conclusion, this study shows pink guava puree supplementation increase antioxidant enzyme activity in SHR’s blood concentration.